REINTERPRETASI PSIKOANALISA FANA’ IMAM AL-JUNAID DALAM MASYARAKAT URBAN - Pratama, Lukman Nugraha (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2024)
Globalization creates harmony between material and spiritual aspects. This phenomenon results in a spiritual crisis which is characterized by a decline in religious values ​​and worship practices that lose their meaning. In this context, this research examines Imam Junaid's concept of fana' and its implementation in the living environment of urban society. By using library research methods and Sigmund Freud's psychoanalytic approach, this research shows that Imam Junaid's concept of fana' can be an effective spiritual solution to face the challenges of the digital era. Through psychoanalytic reinterpretation, this concept is relevant and applicable to pragmatic and rational modern society. It can be a concrete strategy such as controlling consumerism, building strong life principles, and achieving self-awareness amidst the hustle and bustle of urban areas. However, the main challenge lies in bridging the gap between classical spiritual concepts and contemporary reality, and ensuring that its spiritual essence is not reduced to a purely psychological phenomenon. The effectiveness of implementing this concept in overcoming concrete problems in urban communities still requires further evaluation and research